RETRACTED : Peningkatan Kelarutan dan Laju Disolusi Glimepirid Melalui Metode Kokristalisasi - Fitrianti Darusman; Sundani N Soewandhi; Rachmat Mauludin (Indonesian Journal of Pharmaceutical Science and Technology, 2017)
This article was retracted due to duplicate publishing. Authors were confirmed that their article was double publishing. Since this article is retracted, Editors of IJSPT are not responsible for the content of this article. See more the policy of retraction at http://jurnal.unpad.ac.id/ijpst/about/editorialPolicies#custom-3.